2007
DOI: 10.1007/s11663-007-9087-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Viscosities in CaO-SiO2-MgO-Al2O3 and CaO-SiO2-MgO-Al2O3-TiO2 Slags

Abstract: The viscosities of high alumina blast furnace slags were experimentally determined by the rotating cylinder method using the Brookfield digital viscometer model LVDV-II+ pro. Two different slag systems were considered for the current study, the CaO-SiO 2 -MgO-Al 2 O 3 quaternary and the CaO-SiO 2 -MgO-Al 2 O 3 -TiO 2 quinary system. Experiments were conducted in the temperature range of 1650 to 1873 K. The effects of temperature, basicity, TiO 2 , and silica activity of slags on viscosity were studied. The vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 9 publications
8
79
2
2
Order By: Relevance
“…It is well known that FeO and MnO can decrease the viscosity. [25][26][27][28] TiO2 was also reported to decrease the viscosity based on the experimental study carried out by Shankar et al 9) and Park et al 29) Effect of sulphur on the viscosity of BF slag is still not clear. Lower viscosities of the industrial BF slag comparing to the synthetic slags are combined results of all minor components.…”
Section: Comparison Of Viscosities Between Industrial Slagmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that FeO and MnO can decrease the viscosity. [25][26][27][28] TiO2 was also reported to decrease the viscosity based on the experimental study carried out by Shankar et al 9) and Park et al 29) Effect of sulphur on the viscosity of BF slag is still not clear. Lower viscosities of the industrial BF slag comparing to the synthetic slags are combined results of all minor components.…”
Section: Comparison Of Viscosities Between Industrial Slagmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] However, significant discrepancies exist for the reported viscosity data due to the difficulties of high temperature viscosity measurement. In addition to the major components Al2O3, CaO, MgO and SiO2, up to 5 wt% of other components, such as S, TiO2, MnO and FeO may also be present in the BF slags.…”
Section: Introductionmentioning
confidence: 99%
“…9,[15][16][17][18] Ohno and Ross 13) found TiO2 additions increase the slag viscosity in the CaO-SiO2-Al2O3-TiO2 slags under reducing atmospheres of C/CO equilibrium. Shankar et al 19) revealed the effect of TiO2 in the CaO-SiO2-MgO-Al2O3 slag system, where the viscosity decreased with TiO2 up to 2 mass%. Saito et al 14) found TiO2 lowered the viscosity in the CaO-SiO2-MgO-Al2O3 slag system at 10 mass% and 20 mass% TiO2.…”
Section: Introductionmentioning
confidence: 99%
“…CaO and MgO are important additives for the electric furnace process as well as blast furnace process [11,12]. Generally, basicity and MgO are important factors that can affect a slag viscosity and melting temperature, and have been widely studied for various slag systems [13][14][15][16][17]. He [18] studied for effect of MgO on viscosity of blast furnace slag and showed that the slag viscosity decreased with the increasing of MgO content in a definite range, and it decreased obviously with the increasing of slag basicity.…”
Section: Introductionmentioning
confidence: 99%